Crop diversification for resilient farming: Determinants, challenges and policy implications for smallholder agriculture - Arati, Priyadarshini; Subrat, Pattanaik; Sarba, Narayan Mishra (Plant Science Today, 2026)
Crop diversification is a critical approach to minimizing risks from climatic variability, income instability and nutrition insecurity in cereal-based systems. In Odisha, overdependence on paddy, fragmented landholdings, inadequate irrigation and frequent climatic shocks render diversification indispensable for sustainable agriculture. The current research explores the factors influencing farmers' willingness to adopt crop diversification and identifies the major constraints hindering its spread in Odisha. A multi-stage sampling design was used to select 220 farm households from districts representing contrasting levels of cropping intensity. Data covering the period 2021–2024 were collected through structured surveys and secondary sources. The analysis employed Principal Component Analysis (PCA) to derive key socio-economic dimensions, Probit regression (PR) to estimate the adoption probability and the Garrett ranking to rank the constraints. Five major dimensions - land and income capital, demographic experience, market and institutional access, labour and finance and household labour reserve - were extracted through PCA, explaining a cumulative variance of 77.86 % . Probit regression revealed that land ownership, farm income and extension visits significantly increased the probability of diversification, whereas age, paddy yield, market access and credit access decreased the probability. Garrett ranking identified the most important hurdles as lacking market intelligence (rank I; score 66.05), excessive transportation costs (rank II; 60.76) and expensive labour (rank III; 55.08), followed by pest occurrence (rank IV; 53.12), malpractices by middlemen (rank V; 49.60) and poor irrigation (rank VII; 44.58). The results confirm that resource endowments (owned land and farm income), institutional support (extension services) and infrastructural development (market access and transport costs) strongly influence crop diversification. The study illustrates the need for targeted interventions, including improved market intelligence, accessible credit, decentralized infrastructure and the promotion of climate-resilient crops, to advance diversification, enhance farmer incomes and strengthen food and nutrition security, in alignment with the Sustainable Development Goals.